"What is The SI?” A Proposal for an Educational Adjunct to the Redefinition of the International System of Units - Zimmerman, Neil M.; Newell, David B. (Journal of research of the National Institute of Standards and Technology, 2018)
We discuss how the impending redefinition of the SI system of units might affect the ability of students to understand the link between the units and the new system. The redefinition will no longer define a set of base units, but rather a set of constants of nature, such as the elementary charge, e. We point out that this list of constants need not be the only way to introduce students to the subject, either in class or in textbooks. We suggest an alternative way to introduce high school and undergraduate students to the redefined SI, by suggesting a list of experiments for some units; this list would be completely compatible with the redefined SI, and would have all of the same scientific and technological advantages. We demonstrate by questionnaire results that this alternative is more appealing to students. We hope to spur a discussion amongst teachers regarding this important topic for high school and undergraduate physics courses.